Sommersby - Amiel, Jon, 1948-; Pullman, Bill, 1953-; James Earl Jones; Jodie Foster; Lanny Flaherty; Wendell Wellman; William Windom; Richard Gere (France USA Alcor Films, 1993)
Set in the south of the United States just after the Civil War, Laurel Sommersby is just managing to work the farm without her husband Jack, believed killed in the Civil War. By all accounts, Jack Sommersby was not a pleasant man, thus when he returns, Laurel has mixed emotions. It appears that Jack has changed a great deal, leading some people to believe that this is not actually Jack but an imposter. Laurel herself is unsure, but willing to take the man into her home, and perhaps later into her heart...
Set in the south of the United States just after the Civil War, Laurel Sommersby is just managing to work the farm without her husband Jack...
Daniel Vigne
Languages : English, German, Spanish
Subtitles : English, German, Spanish
Keywords: Drama